PATH-19. CLINICOPATHOLOGIC FEATURES AND OUTCOMES OF HISTOLOGICALLY CONFIRMED ATYPICAL DIFFUSE INTRINSIC PONTINE GLIOMA. (5th November 2018) - Diaz, Alexander; Chiang, Jason; Klimo, Paul; Boop, Frederick; Han, Yuanyuan; Li, Yimei; Patay, Zoltan; Gajjar, Amar; Merchant, Thomas; Baker, Suzanne; Tinkle, Christopher
Abstract: Diffuse intrinsic pontine glioma (DIPG) is predominantly diagnosed clinically, with biopsy often reserved for cases with atypical imaging features and/or symptoms. Outcome data and molecular profiling of DIPG have been limited almost entirely to tumors with typical features. We examined the clinicopathologic characteristics and outcomes of 28 patients with pontine-centered lesions who underwent diagnostic biopsy at our institution from 2003 to 2018 because of atypical MRI findings. The median age at diagnosis was 5.2 years (range, 0.7–17.1), and the median symptom duration pre-diagnosis was 1 month (range, 0–24). Common atypical features included pontine asymmetry, tumor extension into the medulla and cerebellar peduncles, and exophytism. Four patients (14.3%) developed transient neurologic symptoms; one (3.6%) experienced a new, permanent cranial neuropathy; and no biopsy-related deaths occurred. Sixteen of the 28 tumors (57%) were confirmed histologically as DIPGs (WHO grade II–IV gliomas; "atypical DIPG"). Of these 16 cases, H3 K27M status was assessed through immunohistochemistry in 14 (88%) and nine were immunopositive (64.3%). The remainder ("atypical non-DIPGs") were pilocytic astrocytomas (58.3%), gangliogliomas (8.3%), CNS embryonal tumors, NOS (16.7%), or C19MC-altered embryonal tumors with multilayered rosettes (16.7%). With a median follow-up of 28.6 months (range, 3.0 – 173.2), 2-year overall survival (OS) was 72.4%, 83.3%, and 62.2% for the total cohort, atypical non-DIPGs, and atypical DIPGs, respectively (P=NS for all). However, OS with H3 K27M–mutant atypical DIPG was inferior to that with H3 WT atypical DIPG (P=0.003). Compared to OS in a contemporary typical DIPG cohort (N=100), OS was significantly longer for the total atypical cohort, atypical non-DIPGs, and atypical DIPGs (P<0.001 for all), but not significantly different for H3 K27M–mutant atypical DIPGs. Thus, despite atypical imaging features, most lesions were consistent with DIPG. Biopsy contributed to revised diagnosis and management in a large number of cases. Integrative molecular analyses are ongoing.